Quebec platelet disorder is linked to the urokinase plasminogen activator gene (PLAU) and increases expression of the linked allele in megakaryocytes - Diamandis, Maria (American Society of Hematology, 2009)
Quebec platelet disorder (QPD) is an autosomal dominant disorder with high penetrance that is associated with increased risks for bleeding. The hallmark of QPD is a gain-of-function defect in fibrinolysis due to increased platelet content of urokinase plasminogen activator (uPA) without systemic fibrinolysis. We hypothesized that increased expression of uPA by differentiating QPD megakaryocytes is linked to PLAU. Genetic marker analyses indicated that QPD was significantly linked to a 2-Mb region on chromosome 10q containing PLAU with a maximum multipoint logarithm of the odds (LOD) score of +11 between markers D10S1432 and D10S1136. Analysis of PLAU by sequencing and Southern blotting excluded mutations within PLAU and its known regulatory elements as the cause of QPD. Analyses of uPA mRNA indicated that QPD distinctly increased transcript levels of the linked PLAU allele with megakaryocyte differentiation. These findings implicate a mutation in an uncharacterized cis element near PLAU as the cause of QPD.